2014
DOI: 10.1038/srep06450
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Hydrophobic to Hydrophilic Transition in Graphene via Water Splitting Induced by UV Irradiation

Abstract: Although the reversible wettability transition between hydrophobic and hydrophilic graphene under ultraviolet (UV) irradiation has been observed, the mechanism for this phenomenon remains unclear. In this work, experimental and theoretical investigations demonstrate that the H2O molecules are split into hydrogen and hydroxyl radicals, which are then captured by the graphene surface through chemical binding in an ambient environment under UV irradiation. The dissociative adsorption of H2O molecules induces the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
111
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 45 publications
8
111
0
Order By: Relevance
“…Previously, we attempted to tailor the surface property of graphene surface from hydrophobic to hydrophilic using several methods including O 2 plasma, 27,28 O 3 treatment, 29,30 UV irradiation, 31,32 surface chemical doping, 33 and electrical field. 34 …”
mentioning
confidence: 99%
“…Previously, we attempted to tailor the surface property of graphene surface from hydrophobic to hydrophilic using several methods including O 2 plasma, 27,28 O 3 treatment, 29,30 UV irradiation, 31,32 surface chemical doping, 33 and electrical field. 34 …”
mentioning
confidence: 99%
“…These observations indicate that the interface between silica and water is indeed hydrophobic but plasma sputtering alters it by removing the polarized electrons of silica skin. These hydrophobic-hydrophilic transition of ZnO [109], graphene [110], and SiO 2 is beyond the description of the Wenzel-Cassie-Baster's law. However, observations comply with the presently proposed hydrophobicity and the hydrophobic-hydrophilic transition mechanism.…”
Section: Plasma Sputteringmentioning
confidence: 91%
“…Figures 10.15 and 10. 16 show the hydrophobic-hydrophilic transition of ZnO [109] and graphene [110].…”
Section: Uv Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of nanopores by thermal oxidation of SLG helps in the quick diffusion of water adlayers. 28 Low temperature UHV STM studies of water exposure samples of graphene on Ru and Cu metal substrates showed discontinuity in MoirĂ© patterns along the line defects in graphene. 13 Verdaguer et al 26 studied the formation of interfacial water adlayers between FLG and insulating BaF 2 and CaF 2 substrates and found that the IWLs are formed only in the case of the BaF 2 substrate due to the less lattice mismatch with hexagonal (I h ) ice.…”
Section: Introductionmentioning
confidence: 98%